Metabolic Disposition of Luteolin Is Mediated by the Interplay of UDP-Glucuronosyltransferases and Catechol-O-Methyltransferases in Rats - Wang, Liping (Drug Metab Dispos, 2017)
Luteolin partially exerts its biologic effects via its metabolites catalyzed by UDP-glucuronosyltransferases (UGTs) and catechol-O-methyltransferases (COMTs). However, the interplay of UGTs and COMTs in mediating luteolin disposition has not been well clarified. In this study, we investigated the glucuronidation and methylation pathways of luteolin mediated by the interplay of UGTs and COMTs in vivo and in vitro. A total of nine luteolin metabolites was detected in rat plasma and bile by liquid chromatography–tandem mass spectrometry, namely, three glucuronides, two methylated metabolites, and four methylated glucuronides. Luteolin-3′-glucuronide (Lut-3′-G) exhibited the highest systemic exposure among these metabolites. Kinetics studies in rat liver S9 fractions suggested two pathways, as follows: 1) Luteolin was glucuronidated to luteolin-7-glucuronide, luteolin-4′-glucuronide, and Lut-3′-G by UGTs, and then Lut-7-G was methylated to chrysoeriol-7-glucuronide and diosmetin-7-glucuronide by COMTs. 2) Alternatively, luteolin was methylated to chrysoeriol and diosmetin by COMTs, and then chrysoeriol and diosmetin were glucuronidated by UGTs to their respective glucuronides. The methylation rate of luteolin was significantly increased by the absence of glucuronidation, whereas the glucuronidation rate was increased by the absence of methylation, but to a lesser extent. In conclusion, two pathways mediated by the interplay of UGTs and COMTs are probably involved in the metabolic disposition of luteolin. The glucuronidation and methylation of luteolin compensate for each other, although glucuronidation is the predominant pathway.